2018
DOI: 10.1016/j.chemosphere.2018.04.021
|View full text |Cite|
|
Sign up to set email alerts
|

Toxicogenetic study of omeprazole and the modulatory effects of retinol palmitate and ascorbic acid on Allium cepa

Abstract: Omeprazole (OME) is a proton pump inhibitor used for the treatment of various gastric and intestinal disease; however, studies on its effects on the genetic materials are still restricted. The present study aimed to evaluate possible toxicogenic effects of OME in Allium cepa meristems with the application of cytogenetic biomarkers for DNA damage, mutagenic, toxic and cytotoxic effects. Additionally, retinol palmitate (RP) and ascorbic acid (AA) were also co-treated with OME to evaluate possible modulatory effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…Compounds. New thiazole derivatives N(5benzyl1,3thiazol2yl)3,5dimethyl 1-benzofuran-2-carboxamide (compound 1) [6] and 8methyl2Me7[3CFphenilme thyl]pyrazolo [4,3e] [1,3]thiazolo [3,2a]pyrimidin4(2H)ones (compound 2) [7] were synthesized at the Department of Organic Chemistry of Ivan Franko National University of Lviv, Ukraine. 10 mM stock solutions were prepared in the Dimethyl sulfoxide (DMSO, SigmaAldrich, USA), and the working solutions were prepared using distilled water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds. New thiazole derivatives N(5benzyl1,3thiazol2yl)3,5dimethyl 1-benzofuran-2-carboxamide (compound 1) [6] and 8methyl2Me7[3CFphenilme thyl]pyrazolo [4,3e] [1,3]thiazolo [3,2a]pyrimidin4(2H)ones (compound 2) [7] were synthesized at the Department of Organic Chemistry of Ivan Franko National University of Lviv, Ukraine. 10 mM stock solutions were prepared in the Dimethyl sulfoxide (DMSO, SigmaAldrich, USA), and the working solutions were prepared using distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Anatelophase test in the mitotic root cells of Allium cepa is widely used plant bioassay in the genotoxicity studies. This test has been applied to investigate genotoxicity of different chemicals [3,11,14,15], anticancer drugs, for example, cisplatin, 5fluorouracil, imatinib mesylate [17], gambogic acid [20], alkylating agents (ethyl methanesulphonate), and methyl methanesulphonate [5,14], food synthetic flavors [2] and nanoparticles [4,12,13,16]. Bagatini et al also used Allium cepa test to evaluate genotoxic effects of hospital effluent in Brasil.…”
Section: Introductionmentioning
confidence: 99%
“…In non-clinical studies, OME toxicogenic effects were identified in plant cells ( Allium cepa) [ 13 ], as well as Saccharomyces cerevisiae and murine Sarcoma 180 cells [ 75 ]. Thus, based in previous investigations, the present study aimed to evaluate cytogenetic damages in patients whith gastritis undergoing OME therapy, with and without H. pylori co-infection, through micronucleus test and expression of catalase and superoxide dismutase.…”
Section: Introductionmentioning
confidence: 99%
“…In non-clinical studies, toxicogenic effects of OME were identi ed in Allium cepa (Braga et al, 2018), as well as oxidative effects in Saccharomyces cerevisiae and cytogenetics in Sarcoma 180 cells (Paz et al, 2019). Thus, in continuity with the previousinvestigations, the present study aimed to evaluate the possible cytogenetic damages of the use and/or therapy of OME in the gastric epithelium of patients with gastritis, with and without H. pylori infection, by the application of the micronucleus test and dosages of catalase and superoxide dismutase.…”
Section: Introductionmentioning
confidence: 99%